GIG Economy: A Bibliometric Analysis - Ali İhsan Balcı; Ersin Eraslan (Sosyal Siyaset Konferansları Dergisi, 2023)
This study used bibliometric analysis to scrutinize the extant literature on the gig economy and examine how it reflects the GIG economy’s impact on society and workers. The concept of the gig economy is widely debated in diverse countries, especially given the recent pandemic. A significant surge has been noted in overseas publications on this topic in the last few years. However, the number of publications on the gig economy remains remarkably limited in Turkey. The advantages and disadvantages of the gig economy will significantly impact the dynamics of the Turkish labor market in the near future, both in terms of work-related life and social effects. The study’s findings suggest that future discussions in the Turkish labor market will focus predominantly on the advantages and disadvantages of the gig economy. The advantages include flexible working hours and independent working relationships. The drawbacks comprise low wages and deviations from the standard social security norms. Additional research is imperative considering the relative novelty and incomplete establishment of Turkish literature on this subject.